IDENTITY AND COOPERATIVE COMPETITIVENESS THROUGH THE ICA GRID MODEL APPROACH (Study on Cooperative of Cattle Farming) - Dandan Irawan (Research Collaboration Community (RCC), 2023)
Cooperatives as a business entity are expected to have a competitive advantage compared to other business entities, thereby providing optimal service to members. In running this business, cooperatives are companies and organizations, so in carrying out their activities they consistently carry out a cooperative identity. For this reason, this study was conducted to find out how the competitive advantages of cooperatives consistently carry out cooperative identity by using the ICA Grid instrument. This research is a case study and was held in Koperasi Pertenak Sapi Bandung Selatan (The Cooperative of Cattle Farmer in South of Bandung) that cooperatives must have a greater role in their business activities.